Beuma Tradition as a Form of Social Solidarity in the Dayak Kebahan Tribe - Shelvyra, Nadia; Bahari, Yohanes; Imanulyaqin, Muhammad Nur; Ramadhan, Iwan; Utami, Patrisia Rahayu (Universitas Tanjungpura, 2025)
This study aims to analyze the forms and roles of social solidarity within the Beuma tradition practiced by the Dayak Kebahan community in Entogong Village, Kayan Hulu District, Sintang Regency. The Beuma tradition, a traditional farming system carried out collectively (berari-ari), reflects the social and cultural values that have been passed down from generation to generation. It not only serves as a means of fulfilling livelihood needs but also strengthens communal bonds and preserves ancestral heritage. This research employed a qualitative approach with a descriptive method to obtain an in-depth understanding of the Beuma tradition. Data were collected through in-depth interviews, participatory observation, and documentation involving traditional leaders and community members who actively participate in Beuma. The data were analyzed through data reduction, presentation, and conclusion drawing to identify patterns of social interaction and solidarity among participants. The results indicate that the Beuma tradition embodies strong social solidarity based on shared values, cooperation, and mutual assistance among community members. Social cohesion is maintained through collective participation in every stage of Beuma, adherence to customary norms, and shared experiences that create emotional bonds and a sense of togetherness. These elements form both mechanical and organic solidarity within the community. The Beuma tradition thus functions not only as an agricultural activity but also as a social system that sustains cultural identity and reinforces harmony amid modernization